Efektivitas Penggunaan Media Pembelajaran Google Classroom Terhadap Hasil Belajar Siswa Kelas X Mata Pelajaran Akuntansi - Lestasi, Ayu Pipih; Tiara, Tiara; Kantun, Sri (Jurnal Pendidikan Ekonomi (JUPE), 2022)
Online learning during the COVID-19 pandemic is an alternative to do so that learning activities can continue. The implementation of this learning requires learning media such as Google Classroom. This application has the advantage of facilitating structured and systematic learning activities. SMKN Darul Ulum Muncar is one of the schools that has not implemented the use of learning media. So researchers are interested in conducting research related to the use of Google Classroom to determine its effect on learning outcomes. This research is an experimental study with a Quasi-Experimental model using the Nonequivalent Control Group Design. The sample required consists of control and experimental groups. The results of the independent sample t-test analysis showed that the sig. (2 tailed) 0.00 < 0.05 so H0 is rejected and Ha is accepted, meaning that there is a significant difference in student learning outcomes between the control and experimental groups. This difference can be seen based on the average value of the experimental group, which is 81.6, which is higher than the control group, which is 68.1. So, it can be concluded that the use of Google Classroom is effective on learning outcomes. However, there are still some obstacles such as difficulties in the coordination process, limitations in supervising student activities, difficulties in shaping students’ character and skills, and inadequate student facilities